Substate dictatorship : networks, loyalty, and institutional change in the Soviet Union - Gorlizki, Yoram, 1963- 1963- (Yale-Hoover Series on Authoritarian Regimes, 2020)
An essential exploration of how authoritarian regimes operate at the local level